Estimasi Tingkat Penetrasi Fotovoltaik Atap pada Jaringan Distribusi Tenaga Listrik yang Terkendala Kualitas Daya: Studi Kasus di Feeder Salodong - Muhammadia, Khayrunnisa B; Jufri, Fauzan Hanif; Husnayain, Faiz (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2025)
The growth of rooftop photovoltaic (PV) systems in Indonesia has increased rapidly as part of the national effort to develop decentralized renewable energy. PT PLN (Persero) North Makassar Customer Service Unit, with a total of 409,025 customers and an installed capacity of 1,332 MVA, has integrated seven rooftop photovoltaic customers with a total capacity of 419.5 kilowatt peak (kWp). The main challenge of integrating rooftop photovoltaics is the system's ability to channel solar energy while maintaining service and operational standards. This research investigates the impact of rooftop PV penetration on power quality parameters, including voltage fluctuations, harmonics, and distribution system reliability in one of the feeders of the PLN North Makassar area. The Salodong feeder, in particular, consists of 137 transformers with a total capacity of 32.9 MVA, serving customers from various tariff groups, including industry, business, social, and residential. The impact of rooftop photovoltaic penetration on the distribution system is evaluated by analyzing various levels of rooftop photovoltaic penetration. Additionally, this study also proposes strategic recommendations that can be implemented to optimize rooftop photovoltaic penetration. The findings highlight a critical penetration threshold, which, if exceeded, will affect power quality limits and propose mitigation strategies to avoid excessive reverse power, high harmonics, and voltage fluctuations. An optimal rooftop photovoltaic penetration level of approximately 30% is recommended, serving as a reference for the PT PLN (Persero) network planning team to enhance PV integration while maintaining system performance.